Pemetaan Produksi Tanaman Tomat di Indonesia Berdasarkan Provinsi Menggunakan Algoritma K-Means Clustering - Syaifuddin Syaifuddin; Ramlah Ramlah; Irma Hakim; Yunida Berliana; Nurhayati Nurhayati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Tomato is one of the essential horticultural commodity vegetables because it has high economic value. The need for this plant continues to increase along with the increase in population, income levels, and heightened public awareness of the importance of nutritional value. Therefore, this research aims to see and map the production of tomato plants in Indonesia by the province in the form of clusters (grouping). The research data used in this paper is data on tomato production in Indonesia by the province in the last five years (2017-2021) obtained from the District/City Agriculture Service of each province and the Indonesian Central Statistics Agency. The algorithm proposed in this study is K-Means Clustering with the help of RapidMiner. The results of the proposed paper are grouping and mapping of tomato production in Indonesia, which is divided into 5 (five) zones, including the Black Zone (areas with very high tomato production), which consists of 1 province, Green Zone (areas with high production of tomatoes). Which consists of 2 provinces, the Blue Zone (areas with moderate production), which consists of 4 provinces. The Light Blue Zone (areas with low production), which consists of 8 provinces, and the Orange Zone (areas with moderately low production), which consists of 18 provinces.